2013
DOI: 10.4248/br201302004
|View full text |Cite
|
Sign up to set email alerts
|

Role and Mechanisms of Actions of Thyroid Hormone on the Skeletal Development

Abstract: The importance of the thyroid hormone axis in the regulation of skeletal growth and maintenance has been well established from clinical studies involving patients with mutations in proteins that regulate synthesis and/or actions of thyroid hormone. Data from genetic mouse models involving disruption and overexpression of components of the thyroid hormone axis also provide direct support for a key role for thyroid hormone in the regulation of bone metabolism. Thyroid hormone regulates proliferation and/or diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
73
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(76 citation statements)
references
References 130 publications
3
73
0
Order By: Relevance
“…On the other hand, thyroxine (T4) replacement induced rapid catch-up growth in juvenile hypothyroidism patients [2,4]. Our laboratory has recently found that THs play a critical role in skeletal development and linear growth during prepuberty when the effects of growth hormone are surprisingly small [4,5]. By contrast, childhood thyrotoxicosis caused accelerated linear growth and bone maturation and resulted in premature fusion of the growth plates and short stature [6].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…On the other hand, thyroxine (T4) replacement induced rapid catch-up growth in juvenile hypothyroidism patients [2,4]. Our laboratory has recently found that THs play a critical role in skeletal development and linear growth during prepuberty when the effects of growth hormone are surprisingly small [4,5]. By contrast, childhood thyrotoxicosis caused accelerated linear growth and bone maturation and resulted in premature fusion of the growth plates and short stature [6].…”
Section: Introductionmentioning
confidence: 95%
“…Thyroid dysfunctions such as juvenile hypothyroidism and a heterozygous mutation of thyroid hormone receptor alpha caused short stature and delayed bone formation and mineralization in humans [1][2][3]. On the other hand, thyroxine (T4) replacement induced rapid catch-up growth in juvenile hypothyroidism patients [2,4]. Our laboratory has recently found that THs play a critical role in skeletal development and linear growth during prepuberty when the effects of growth hormone are surprisingly small [4,5].…”
Section: Introductionmentioning
confidence: 97%
“…Dysregulation in the production and/or actions of any of the factors that regulate endochondral ossification can result in skeletal diseases including chondrodysplasias and osteoarthritis (21, 40). Although the processes leading to POC formation have been well established, signaling pathways that stimulate SOC formation are not well understood.Thyroid hormone (TH) is known to play an important role in normal endochondral ossification and is essential for skeletal development, linear growth, maintenance of bone density, and efficient fracture healing (20,45,47,48). Juvenile hypothyroidism causes dwarfism with delayed bone formation and mineralization, while TH replacement induces rapid catch-up growth (1,20,44,45).…”
mentioning
confidence: 99%
“…Thyroid hormone (TH) is known to play an important role in normal endochondral ossification and is essential for skeletal development, linear growth, maintenance of bone density, and efficient fracture healing (20,45,47,48). Juvenile hypothyroidism causes dwarfism with delayed bone formation and mineralization, while TH replacement induces rapid catch-up growth (1,20,44,45).…”
mentioning
confidence: 99%
See 1 more Smart Citation